1989
DOI: 10.1111/j.1365-2125.1989.tb03424.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective metabolism of metoprolol in Caucasians and Nigerians‐ relationship to debrisoquine oxidation phenotype.

Abstract: The relationship between debrisoquine oxidation phenotype and the stereoselective metabolism of metoprolol was investigated in populations of British Caucasians (n = 139) and Nigerian subjects (n = 117). The 0-8 h urinary S/R-metoprolol (S/R-M) ratio was related to the ability to metabolise metoprolol and debrisoquine in both ethnic groups. The median S/R-M ratio was significantly higher in Caucasians (1.27) than in Nigerians (1.10). In the Caucasian population poor metabolisers of debrisoquine had significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The S/R metoprolol ratios were also found to vary between genotypes, at 1.6, 1.3 and 1.0 for two, one and zero functional alleles, respectively. These findings support the earlier observation in healthy volunteers of stereoselective metabolism of metoprolol, 24,25 suggesting that R-metoprolol is more dependent on CYP2D6 for metabolism than S-metoprolol. In only one of the patient studies, 15 R-metoprolol concentrations were measured and these were not reported specifically.…”
Section: Discussionsupporting
confidence: 82%
“…The S/R metoprolol ratios were also found to vary between genotypes, at 1.6, 1.3 and 1.0 for two, one and zero functional alleles, respectively. These findings support the earlier observation in healthy volunteers of stereoselective metabolism of metoprolol, 24,25 suggesting that R-metoprolol is more dependent on CYP2D6 for metabolism than S-metoprolol. In only one of the patient studies, 15 R-metoprolol concentrations were measured and these were not reported specifically.…”
Section: Discussionsupporting
confidence: 82%
“…32,36,37 In Nigerian and South African populations, however, poor debrisoquine metabolizers were not phenotyped as poor metoprolol metabolizers. 19 The results showed enantioselectivity in the pharmacokinetics of metoprolol, with observation of higher areas under the plasma concentration versus time curves for (S)-metoprolol compared to its antipode (P < .05) as consequence of a lower Cl T /f for this enantiomer, and resulted in mean AUC (S)-/AUC (R)-ratios of 1.21. Enantiomeric ratios of 1.39 were reported by Johnson and Burlew 5 in the investigation of healthy volunteers treated with a single dose of racemic metoprolol, and ratios of 1.29 were reported by Cerqueira et al 8 somes.…”
Section: Discussionmentioning
confidence: 88%
“…CYP2D6 genotype‐phenotype correlates with differences in metoprolol pharmacokinetics 17 . In addition to the oxidative phenotype, enantioselectivity in the pharmacokinetics of metoprolol administered orally to extensive metabolizers (EM) is highly relevant in terms of the wide interindividual variability observed in the kinetic disposition of this drug 6 , 8 , 18 , 19 . It is known that genetic factors play a preponderant role in stereoselectivity; however, the influence of diseases has been surprisingly little investigated.…”
mentioning
confidence: 99%
“…Approximately 70% of the total metabolism of metoprolol (O-demethylation and ahydroxylation) is dependent on CYP2D6 [26]. Earlier studies have shown that PM individuals have higher plasma metoprolol concentrations than EMs when given standard doses of the drug [27], the S/R ratio of metoprolol enantiomers is lower in PMs since the concentration of the inactive R-metoprolol is increased more clearly [28]. Koytchev et al [29] studied the in¯uence of the CYP2D6*4 allele on the pharmacokinetics of controlled-release metoprolol.…”
Section: B-adrenoceptormentioning
confidence: 99%